2023
DOI: 10.3390/ma16124345
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolized Diatomaceous Biomass Doped with Epitaxially Growing Hybrid Ag/TiO2 Nanoparticles: Synthesis, Characterisation and Antibacterial Application

Abstract: In the pursuit of innovative solutions for modern technologies, particularly in the design and production of new micro/nanostructured materials, microorganisms acting as “natural microtechnologists” can serve as a valuable source of inspiration. This research focuses on harnessing the capabilities of unicellular algae (diatoms) to synthesize hybrid composites composed of AgNPs/TiO2NPs/pyrolyzed diatomaceous biomass (AgNPs/TiO2NPs/DBP). The composites were consistently fabricated through metabolic (biosynthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 84 publications
(100 reference statements)
0
0
0
Order By: Relevance
“…On the other hand, the support used for the nanocomposites preparation can also influence the antimicrobial activity once the formulations obtained in the present research display a lower MIC value (1.25 mg/mL) compared to the based AgNPs/kaolinite [47], whereas AgNPs/TiO 2 /DBP [43] nanocomposite where the MIC value was found to be ranged between 2.5 and 10 mg/mL against the same bacterial strains. Furthermore, noteworthy the fact that DBioSiO 2 (unmodified matrix) used in the present study as support exhibits antimicrobial activity compared to the TiO 2 /DBP and kaolinite support that have not displayed any move against the same bacterial strains.…”
Section: Antibacterial Activity Assaymentioning
confidence: 73%
See 2 more Smart Citations
“…On the other hand, the support used for the nanocomposites preparation can also influence the antimicrobial activity once the formulations obtained in the present research display a lower MIC value (1.25 mg/mL) compared to the based AgNPs/kaolinite [47], whereas AgNPs/TiO 2 /DBP [43] nanocomposite where the MIC value was found to be ranged between 2.5 and 10 mg/mL against the same bacterial strains. Furthermore, noteworthy the fact that DBioSiO 2 (unmodified matrix) used in the present study as support exhibits antimicrobial activity compared to the TiO 2 /DBP and kaolinite support that have not displayed any move against the same bacterial strains.…”
Section: Antibacterial Activity Assaymentioning
confidence: 73%
“…Many research studies demonstrated the antimicrobial activity, synergistic effect of silver formulations against clinical isolates and its application in pharmacology and cosmetology [44][45][46]. In another trend of thoughts, our previous studies [43,47] show dissimilarity in the antimicrobial activity of AgNPs/kaolinite and AgNPs/TiO 2 /DBP nanocomposites that used additional support for the synthesis. Additionally, the support influences the antimicrobial effect, the metal (element) used, and the synthesis method; the TiO 2 /DBP nanocomposites display higher antimicrobial potential against the same bacterial strains than AgNPs/ kaolinite.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation